2021
DOI: 10.1007/s10565-021-09603-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental toxicity assessment of flame retardants using a human DNT in vitro testing battery

Abstract: Due to their neurodevelopmental toxicity, flame retardants (FRs) like polybrominated diphenyl ethers are banned from the market and replaced by alternative FRs, like organophosphorus FRs, that have mostly unknown toxicological profiles. To study their neurodevelopmental toxicity, we evaluated the hazard of several FRs including phased-out polybrominated FRs and organophosphorus FRs: 2,2′,4,4′-tetrabromodiphenylether (BDE-47), 2,2′,4,4′,5-pentabromodiphenylether (BDE-99), tetrabromobisphenol A, triphenyl phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 126 publications
5
32
0
Order By: Relevance
“…The PeriTox test is a well established in vitro screening assay using human iPSC-derived peripheral neurons to identify peripheral neurotoxicants [28]. It has been successfully used to identify environmental neurotoxicants by assessing their effects on the neurite structures [40][41][42]. However, for pre-clinical drug testing, an increased sensitivity in detecting the potential neurotoxicity of chemotherapeutics is desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PeriTox test is a well established in vitro screening assay using human iPSC-derived peripheral neurons to identify peripheral neurotoxicants [28]. It has been successfully used to identify environmental neurotoxicants by assessing their effects on the neurite structures [40][41][42]. However, for pre-clinical drug testing, an increased sensitivity in detecting the potential neurotoxicity of chemotherapeutics is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test, whether also functional properties were similar, we investigated toxicant-sensitivity. The PeriTox test, a well established screening assay [40][41][42], was used to assess effects on the neurite area and the cell viability of immature neurons on DoD0.…”
Section: Human Ipsc-derived Peripheral Neurons For Toxicity Testingmentioning
confidence: 99%
“…Thus, we believe the argument that safety is ensured because typical human exposures are below the reference dose (when known) has not been demonstrated. Also important is that human exposures occur throughout lifetimes to complex mixtures of flame retardants and plasticizers, which may have additive or synergistic effects that are not accounted for in current regulatory assessments (Klose et al 2021). Such exposures are rapidly increasing on a global scale (Blum et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using a battery of cell-based and in vitro assays have reported compromised neurodifferentiation, neurite outgrowth, and electrical activity by numerous OPEs (Behl et al 2015;Hausherr et al 2014;Shafer et al 2019), sometimes at concentrations lower than for known neurotoxic OPPs (Dishaw et al 2014a;Ryan et al 2016). Furthermore, other key processes involved in neurodevelopment-such as proliferation, migration, and oligodendrocyte differentiation-have been shown to be affected by exposure to OPEs (Klose et al 2021).…”
Section: Nonmammalian and In Vitro Modelsmentioning
confidence: 99%
“…As cell source, we used NCCs differentiated from pluripotent stem cells. Such cells have been characterized by comprehensive transcriptome analysis, and they have been used successfully as test system for in vitro assays (Nyffeler et al, 2017a;Pallocca et al, 2017;Zimmer et al, 2014;Klose et al, 2021;Lee et al, 2010).…”
Section: Establishment Of a Chemotaxis Assay Based On Human Ncsmentioning
confidence: 99%